2001
DOI: 10.1677/joe.0.1690079
|View full text |Cite
|
Sign up to set email alerts
|

Human uterine myometrial smooth muscle cell proliferation and vascular endothelial growth-factor production in response to platelet-derived growth factor

Abstract: It has been recognized that tissue-specific growth factors and angiogenic factors play important roles in the growth of tumors and in the tissue-repair system. In uterine myometrial smooth muscle cells, it has also been reported that the platelet-derived growth factor (PDGF) binds to PDGF receptors and stimulates proliferation. In this paper, we examine whether or not PDGF is able to stimulate production of vascular endothelial growth factor (VEGF) in cultured human myometrial smooth muscle cells. PDGF treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…PDGF stimulates DNA synthesis as well as protein synthesis (Fayed et al, 1989), increases collagen alpha1 expression (Liang et al, 2006) and modulates the rate of cell proliferation in myometrium and leiomyoma cells (Arici and Sozen, 2003;Liang et al, 2006). Taniguchi et al (2001) examined whether or not PDGF would be able to stimulate the expression of VEGF in cultured human myometrial smooth muscle cells. They reported that PDGF treatment enhanced VEGF immunoreactivity and stimulated cell proliferation (Taniguchi et al, 2001).…”
Section: Uterine Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDGF stimulates DNA synthesis as well as protein synthesis (Fayed et al, 1989), increases collagen alpha1 expression (Liang et al, 2006) and modulates the rate of cell proliferation in myometrium and leiomyoma cells (Arici and Sozen, 2003;Liang et al, 2006). Taniguchi et al (2001) examined whether or not PDGF would be able to stimulate the expression of VEGF in cultured human myometrial smooth muscle cells. They reported that PDGF treatment enhanced VEGF immunoreactivity and stimulated cell proliferation (Taniguchi et al, 2001).…”
Section: Uterine Effectsmentioning
confidence: 99%
“…Taniguchi et al (2001) examined whether or not PDGF would be able to stimulate the expression of VEGF in cultured human myometrial smooth muscle cells. They reported that PDGF treatment enhanced VEGF immunoreactivity and stimulated cell proliferation (Taniguchi et al, 2001). Mesquita et al (2010) demonstrated that NADPH oxidasederived ROS is a necessary component of the MAP kinase mitogenic pathway activated by PDGF in leiomyoma smooth muscle cells.…”
Section: Uterine Effectsmentioning
confidence: 99%
“…Both EGF and PDGF receptors have previously been identified in LSMCs [9,10]. Furthermore, EGF and PDGF have been shown by numerous investigators to stimulate the proliferation of LSMCs [9,11]. Vascular SMCs show similar mitogenic responses to these same growth factors [12,13].…”
Section: Introductionmentioning
confidence: 97%
“…More recently, several laboratories have shown that several primary cell types, immortalized by stable transfection with an expression vector for the catalytic subunit of human telomerase (hTERT), maintain normal karyotype and phenotype (Greider, 1996;Bodnar et al, 1998;Vaziri and Benchimol, 1998;Wang et al, 1998). Telomeres are specialized DNA repeats at the ends of chromosomes that gradually become shorter with succeeding cell EGF binding and stimulation of growth Bhargava et al, 1979 EGF EGF and platelet-derived growth factor receptors Rossi et al, 1992 EGF EGF action Kornyei et al, 1995 Transforming growth factor (TGF) Autocrine/paracrine TGFb system Tang et al, 1997 TGF Gestational changes in the levels of TGF-b1 and TGFb receptor types I and II Hatthachote et al, 1998 TGF Matrix metalloproteinases and their tissue inhibitors Ma and Chegini, 1999 TGF Parathyroid hormone-related protein secretion and cAMP production Shenberger et al, 2001 Insulin-like growth factor (IGF)-I Tissue localization and action of IGF-I receptors and IGF binding proteins 1-4 Tang et al, 1994 IGF-I IGF-I regulation of IGF binding protein-3 and -4 Huynh, 2000 Basic fibroblast growth factor (bFGF) Mitogenic effects of bFGF and estradiol Rauk et al, 1995 Vascular endothelial growth factor (VEGF) VEGF receptor tyrosine kinases Brown et al, 1997 Platelet-derived growth factor Stimulation of VEGF production Taniguchi et al, 2001 Heparin-binding growth factor…”
Section: Introductionmentioning
confidence: 99%